2021
DOI: 10.21203/rs.3.rs-470171/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiac Involvement in Patients Recovered From COVID-19 Identified Using Left Ventricular Longitudinal Strain

Abstract: Coronavirus disease-19 (COVID-19) has been associated with subclinical myocardial dysfunction during its acute phase and a recurring pattern of reduced basal left ventricular longitudinal strain on speckle-tracking echocardiography (STE) in hospitalized patients. But a question still remains unanswered: speckle tracking echocardiography might also be suitable to detect residual myocardial involvement after acute stage of COVID-19? Methods and results: We studied 100 patients recovered from COVID-19 with STE to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
(36 reference statements)
0
7
0
2
Order By: Relevance
“…Another study included 100 patients recovered from COVID-19 at a median delay of 130 days. Overall GLS was not reduced in post-COVID patients, but the basal segmental longitudinal strain was found to be lower [13]. Yet another study included 86 COVID-19 survivors late (median time interval 327 days) after recovery.…”
Section: Limitationsmentioning
confidence: 92%
See 4 more Smart Citations
“…Another study included 100 patients recovered from COVID-19 at a median delay of 130 days. Overall GLS was not reduced in post-COVID patients, but the basal segmental longitudinal strain was found to be lower [13]. Yet another study included 86 COVID-19 survivors late (median time interval 327 days) after recovery.…”
Section: Limitationsmentioning
confidence: 92%
“…Only a few studies have reported GLS in patients recently recovered from COVID-19 [12][13][14]. A study from North India included 134 subjects within 30-45 days after recovery from COVID-19 [12].…”
Section: Limitationsmentioning
confidence: 99%
See 3 more Smart Citations